2023
DOI: 10.1136/archdischild-2023-325399
|View full text |Cite
|
Sign up to set email alerts
|

Childhood/adolescent Sydenham’s chorea in the UK and Ireland: a BPSU/CAPSS surveillance study

Abstract: ObjectiveTo conduct the first prospective surveillance study of Sydenham’s chorea (SC) in the UK and Ireland, and to describe the current paediatric and child psychiatric service-related incidence, presentation and management of SC in children and young people aged 0–16 years.DesignSurveillance study of first presentations of SC reported by paediatricians via the British Paediatric Surveillance Unit (BPSU) and all presentations of SC reported by child and adolescent psychiatrists through the Child and Adolesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“… 1 , 13 Only 3 small randomized clinical trials (RCTs) assessing immunotherapy for SC have been reported, 14 , 15 , 16 and treatment strategies vary widely, with corticosteroid use in recent cohorts ranging from 16% to 75%, and steroid regimens differing even within centers. 17 , 18 , 19 , 20 Herein we present a comprehensive evidence synthesis of published SC cases with individual patient data (IPD), with the aims of describing the clinical features and management of SC and of identifying associations between early clinical and treatment factors and disease course and outcome.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 13 Only 3 small randomized clinical trials (RCTs) assessing immunotherapy for SC have been reported, 14 , 15 , 16 and treatment strategies vary widely, with corticosteroid use in recent cohorts ranging from 16% to 75%, and steroid regimens differing even within centers. 17 , 18 , 19 , 20 Herein we present a comprehensive evidence synthesis of published SC cases with individual patient data (IPD), with the aims of describing the clinical features and management of SC and of identifying associations between early clinical and treatment factors and disease course and outcome.…”
Section: Introductionmentioning
confidence: 99%